Relationships and significance of lactate minimum, critical velocity, heart rate deflection and 3 000 m track-tests for running" - Simoes, H. G.; Denadai, B. S.; Baldissera, V.; Campbell, C. S. G.; Hill, D. W. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: The running velocities associated to lactate minimum (Vlm), heart rate deflection (VHRd), critical velocity (CV), 3.000 m (V3000) and 10 000 m performance (V10km) were compared. Additionally the ability of Vlm and VHRd on identifying sustainable velocities was investigated. Methods: Twenty runners (28.5±5.9 y) performed 1) 3 000 m running test for V3000; 2) an all-out 500 m sprint followed by 6¥800 m incremental bouts with blood lactate ([lac]) measurements for Vlm; 3) a continuous velocity-incremented test with heart rate measurements at each 200 m for VHRd; 4) participants attempted to 30 min of endurance test both at Vlm(ETVlm) and VHRd(ETVHRd). Additionally, the distance-time and velocity-1/time relationships produced CV by 2 (500 m and 3 000 m) or 3 predictive trials (500 m, 3 000 m and distance reached before exhaustion during ETVHRd), and a 10 km race was recorded for V10km. Results: The CV identified by different methods did not differ to each other. The results (m.min-1) revealed that Vlm (281±14.8)<CV (292.1±17.5)=V10km (291.7±19.3)<VHRd (300.8±18.7)=V3000 (304±17.5) with high correlation among parameters (P<0.001). During ETVlm participants completed 30 min of running while on the ETVHRd they lasted only 12.5±8.2 min with increasing [lac]. Conclusion: We evidenced that CV and Vlm track-protocols are valid for running evaluation and performance prediction and the parameters studied have different significance. The Vlm reflects the moderate-high intensity domain (below CV), can be sustained without [lac] accumulation and may be used for long-term exercise while the VHRd overestimates a running intensity that can be sustained for long-time. Additionally, V3000 and VHRd reflect the severe intensity domain (above CV).